Loss of Serine-Type D-Ala-D-Ala Carboxypeptidase DacA Enhances Prodigiosin Production in Serratia marcescens - Pan, Xuewei; Sun, Changhao; Tang, Mi; Liu, Chao; Zhang, Jianing; You, Jiajia; Osire, Tolbert; Sun, Yang; Zhao, Youxi; Xu, Meijuan; Yang, Taowei; Rao, Zhiming (Frontiers in Bioengineering and Biotechnology, 2019)
Serratia marcescens, a gram-negative bacterium, found in a wide range of ecological niches can produce several high-value products, including prodigiosin, althiomycin, and serratamolide. Among them, prodigiosin has attracted attention due to its immunosuppressive, antimicrobial and anticancer properties. However, the regulatory mechanisms behind prodigiosin synthesis in Serratia marcescens remains limited. Here, a transposon mutant library was constructed to identify the genes related to prodigiosin synthesis, and BVG90_02415 gene encoding a peptidoglycan synthesizing enzyme D-Ala-D-Ala carboxypeptidase DacA was found to negatively regulates prodigiosin synthesis. Quantitative measurements revealed that disruption of dacA increased prodigiosin production 1.46-fold that of the wild-type strain JNB5-1 in fermentation medium. By comparing differences in cell growth, pigA gene expression level, cell morphology, membrane permeability, and intracellular prodigiosin concentration between wild-type strain JNB5-1 and dacA mutant SK4-72, results revealed that the mechanism for hyper-producing of prodigiosin by the dacA mutant was probably that dacA disruption enhanced prodigiosin leakage, which in turn alleviated feedback inhibition of prodigiosin and increased expression of pig gene cluster. Collectively, this work provides a novel insight into regulatory mechanisms of prodigiosin synthesis and uncovers new roles of DacA protein in regulating cell growth, cell morphology, and membrane permeability in Serratia marcescens. Finally, this study offers a new strategy for improving production of high-value compounds in Serratia marcescens.